The Value of Voltage Histogram Analysis Derived Right Atrial Scar Burden in the Prediction of Left Atrial Scar Burden - Szilvia Herczeg; Joseph Galvin; John J. Keaney; Edward Keelan; Roger Byrne; Claire Howard; Laszlo Geller; Gabor Szeplaki (Cardiology Research and Practice)
Introduction. Growing evidence suggests that fibrotic changes can be observed in atrial fibrillation (AF) in both atria. Quantification of the scar burden during electroanatomical mapping might have important therapeutic and prognostic consequences. However, as the current invasive treatment of AF is focused on the left atrium (LA), the role of the right atrium (RA) is less well understood. We aimed to characterize the clinical determinates of the RA low-voltage burden and its relation to the LA scaring. Methods. We have included 36 patients who underwent catheter ablation for AF in a prospective observational study. In addition to LA mapping and ablation, high-density RA bipolar voltage maps (HD-EAM) were also reconstructed. The extent of the diseased RA tissue (≤0.5 mV) was quantified using the voltage histogram analysis tool (CARTO®3, Biosense Webster). Results. The percentage of RA diseased tissue burden was significantly higher in patients with a CHA2DS2-VASc score ≥ 2 p=0.0305, higher indexed LA volume on the CTA scan and on the HD‐EAM (p=0.0223 and p=0.0064, respectively), or higher indexed RA volume on the HD‐EAM p=0.0026. High RA diseased tissue burden predicted the presence of high LA diseased tissue burden (OR = 7.1, CI (95%): 1.3–38.9, p=0.0145), and there was a significant correlation of the same (r = 0.6461, p<0.0001). Conclusions. Determining the extent of the right atrial low-voltage burden might give useful clinical information. According to our results, the diseased tissue burden correlates well between the two atria: the right atrium mirrors the left atrium.